Profesionalisme Kinerja Guru Dalam Pembelajaran Pendidikan Agama Islam (PAI) Di SMP Karya Bhakti Negeri Besar Way Kanan - Nurhidayah, Eva; Ehwanudin, Ehwanudin; Mida Hayati, Rina (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2023)
Education is the most important need that must be owned humans, with education the national ideals of the Indonesian people that have been fought for so far will be realized, namely efforts to educate the nation's life through national education, one of which is Islamic Religious Education. Teacher performance is in planning learning, implementing learning and assessing learning outcomes. This research is a qualitative research with a method based on the philosophy of postpositivism. Based on the results of the research that has been done, it can be concluded that the teacher's performance in teaching PAI at SMP Karya Bhakti is in accordance with the Ministry of National Education, which can be seen from the lesson plans such as lesson plans, syllabus, prota and prosem. implementation of learning includes class management, use of media and learning resources, and use of learning methods. And evaluation of learning using written tests and practical tests.